2014
DOI: 10.5254/rct.13.86963
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Low Temperature Resistant and High Electrical Insulation Chloroprene Rubber–butadiene Rubber Blends

Abstract: To satisfy some special demands of many applications in the fields of aerospace and the electronic industry, low temperature resistant and high electrical insulation chloroprene rubber (CR) was prepared by blending pristine CR with different weight ratios of butadiene rubber (BR). The low temperature resistance, electrical insulation properties, and mechanical properties of CR/BR blends were investigated. With increasing BR content, the low temperature resistance and electrical insulation properties were impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The other ingredient of studied composites-chloroprene rubber (CR)-belongs to the group of special elastomers because of its unique characteristics (polar chain structure, good oil resistance and resistance to flame and ozone) [8,9]. On a large scale, the polymerization of chloroprene is carried out during the free radical emulsion polymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other ingredient of studied composites-chloroprene rubber (CR)-belongs to the group of special elastomers because of its unique characteristics (polar chain structure, good oil resistance and resistance to flame and ozone) [8,9]. On a large scale, the polymerization of chloroprene is carried out during the free radical emulsion polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…BR displays low temperature resistance and high electrical insulation properties due to its regular molecular structure, flexible molecular chain and the absence of substituted groups in the main chain. The addition of BR to CR improves low temperature resistance and electrical insulation properties of CR [9]. The elastomeric blend containing chloroprene and butadiene rubbers cross-linked with copper(II) oxide (Cu 2 O) or copper(II) oxide (CuO) was also studied [22].…”
Section: Introductionmentioning
confidence: 99%
“…Chloroprene rubber has recently been combined with other elastomers to achieve special properties of either the CR-based compounds or compounds based on second ingredients. A few reports describe blends of CR with other rubber, such as natural rubber (NR) [10,11], hydrogenated acrylonitrile-butadiene rubber (HNBR) [12,13], styrene-butadiene rubber [14], butadiene rubber (BR) [15,16] or chlorosulfonated polyethylene (CSM) [17] have been published thus far. The Salleh et al [11] investigated two types of blends containing the natural rubber and chloroprene rubber or epoxidized natural rubber and chloroprene rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al studied the blend of CR with butadiene rubber (BR). 11 It was found that the addition of BR could increase the low temperature resistance and electrical insulation but decrease the mechanical properties of the blend. Das et al investigated the physical and electrical properties of CR and natural rubber (NR) blends.…”
Section: Introductionmentioning
confidence: 99%